Pengembangan Agroindustri Olahan Terong Belanda di Kabupaten Wonosobo Jawa Tengah - Eni Istiyanti; Francy Risvansuna Fivintari; Elita Khairunnisaa (Jurnal Riset Agribisnis dan Peternakan, 2020)
Tamarillo has soft characteristics and contains a lot of water so they are easily damaged if stored in fresh form, therefore it is necessary to have post-harvest handling in the form of processing in order to extend the shelf life. The study aims to analyze the costs, income, and profits, as well as the feasibility seen from the R / C, break event point (BEP), and the added value of various tamarillo processed products. The study was conducted in a survey of all tamarillo processed agroindustry in Wonosobo Regency, which amounted to 6 agroindustries. The research method used is descriptive quantitative analysis. The study uses primary data obtained through interviews and secondary data by means of documentation. Tamarillo processed products consist of candied, fruit juice, dodol, wajik, and candied pumpkin. The results showed that the production of candied tamarillo is the most compared to other processed products and can generate the greatest income and profits. All tamarillo processed products are feasible based on R/C, BEP, and value-added criteria. The development of tamarillo agro-industry needs the support of the government and related parties to provide education to consumers about the benefits of tamarillo.